Navigating uncertainty: a strategic framework for early-stage entrepreneurial - Sosa Gómez, Iván (European Public & Social Innovation Review, 2025)
Introduction: This research presents a strategic framework for early-stage entrepreneurial startups, focusing on navigating uncertainty and optimizing resources to create value. Integrating multidisciplinary perspectives across four dimensions - entrepreneurship, opportunity, value, and business model - this research provides actionable insights to enhance decision-making and increase startup success rates. Methodology: Based on the research strategy, entrepreneurship is viewed through managerial theories, highlighting the exploitation of opportunities and resource management as critical to successful entrepreneurship. Grounded in existing literature and enriched with empirical case studies, the entrepreneurial framework validates theoretical constructs and demonstrates real-world applicability. Findings: By expanding the scope of business opportunity, value creation, and business model, this research provides a strategic entrepreneurial framework for navigating the complexities of launching new startups. Contributions: This framework contributes to the field by providing an integrative approach to entrepreneurship that can significantly enhance the effectiveness of entrepreneurial activities, suggesting actionable approaches for entrepreneurs to enhance their decision-making processes and increase the success rate of startups in the early stages. Conclusion: This research offers a robust and practical guide for early-stage entrepreneurship, enhancing decision-making and increasing the potential for entrepreneurial venture survival.